Mycobacterium tuberculosis DosR Regulon Gene Rv2004c Encodes a Novel Antigen with Pro-inflammatory Functions and Potential Diagnostic Application for Detection of Latent Tuberculosis - Doddam, Sankara Narayana (Front Immunol, 2017)
Approximately 1.7 billion people in the world harbor latent Mycobacterium tuberculosis (Mtb) with a substantial risk of progression to clinical outcome. Containment of these seed beds of Mtb is essential to eliminate tuberculosis completely in high burden settings such as India. Hence, there is an urgent need for the identification of new serological markers for detection or vaccine candidates to prevent latent tuberculosis infection (LTBI). DosR regulon antigens of Mtb might serve as attractive targets for LTBI diagnosis or vaccine development as they are specifically expressed and are upregulated during latent phase. In this study, we investigated the role of Rv2004c, a member of DosR regulon (exclusive to Mtb complex), in host–pathogen interaction and its immunogenic potential in LTBI, active TB, and healthy control cohorts. Rv2004c elicited strong antibody response in individuals with LTBI compared to active TB patients and healthy cohorts. Recombinant Rv2004c induced pro-inflammatory cytokine response in human peripheral blood mononuclear cells and THP-1 cells via NF-κB phosphorylation. Interaction of Rv2004c with toll-like receptor (TLR)-2 was confirmed using HEK-Blue hTLR-2 and pull-down assays. Rv2004c enhanced the surface expression of TLR-2 at mRNA and protein levels in THP-1 cells. Our findings revealed that Rv2004c induces strong humoral and cell mediated immune responses. Given these observations, we propose Rv2004c to be a potential diagnostic marker or an attractive vaccine candidate that can be useful against LTBI.